Ensino de matemática financeira e estatística básica - Silva, Luís Henrique Oliveira da [UNESP] (2015)
This project was carried out to try to address the lack of knowledge of financial mathematics and introduce a sense of what is statistics. The target audience is elementary school children from the Presbyterian College of Presidente Prudente, who attend the 8th and 9th grades.